MON-249 SDHD Mutation: Nonfunctional Paragangliomas Presenting as Bilateral Carotid Body Tumors with Syncope - LaChance, David (J Endocr Soc, 2020)
SDHD Mutation: Nonfunctional paragangliomas presenting as bilateral carotid body tumors with syncope Background: A mutation of the SDHD gene is associated with hereditary paraganglioma-pheochromocytoma (PGL/PCC) syndromes which most commonly originate in the head and neck region, and usually form in the carotid body. Paragangliomas (PGL) can be secretory or non-secretory with about 95% of head and neck PGL being non-secretory. They can rarely present with symptoms due to compression, however, as in this case of a 29 year-old female presenting with syncope. Clinical Case: A 29 year-old female presented for evaluation after syncope. She had a syncopal event and fell down while walking in her home. Syncope was preceded by about 15 minutes of flushing, nausea and palpitations. She reported similar episodes once weekly in the preceding months, which generally lasted an hour. Initial workup included normal vital signs at presentation, normal ECG and echocardiogram, normal TFT, CBC, complete metabolic panel. Subsequent head/neck CT revealed bilateral masses in the carotid bifurcations consistent with carotid body tumors. Further history revealed a family history of bilateral carotid body tumors in her father which had never been evaluated. Plasma and urine metanephrines were normal. She underwent carotid body tumor excision. The left carotid body tumor was successfully excised and pathology revealed a paraganglioma with positive synaptophysin and chromogranin stains. Genetic testing revealed an SDHD (succinate dehydrogenase complex subunit D) gene mutation. Repeat biochemical assessment 4 months later was again negative and patient remained asymptomatic postoperatively. Conclusion: Paragangliomas can be secretory or non-secretory with about 95% of head and neck paragangliomas being non-secretory, as in this case. Symptoms can arise from catecholamine hypersecretion, which generally presents as hypertension, headaches, diaphoresis, flushing, anxiety or palpitations, and can be episodic or sustained, or mass effect. Syncope as a presenting symptom is rare, however, and has not been quantified but only reported in case reports. The exact etiology of syncope in our patient is not clear. Hereditary PGL/PCC syndromes should be suspected in any individual with multiple, recurrent, early-onset (age less than 45 years) or family history of PGL/PCC, as these syndromes are inherited in an autosomal dominant manner.